Effect of expected exercise duration on physiological and psychological variables - Lindsay, R.; Gaul, C. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Consideration of the end-point of exercise may influence exercise function. Research has shown that runners expecting a longer exercise duration report lower RPE at the same time point as compared to when they expect a shorter duration at the same intensity (Rejeski & Ribisl, 1980; Baden et al,. 2004). This study examined the effect of expected exercise duration on physiological and psychological variables during cycling. Methods: Twenty trained male cyclists completed a maximal aerobic cycling test and two 20 min bouts at the same submaximal power output (mean=69% VO2max). Subjects were told they would cycle for 20 min in the first bout (short condition) and for 40 min in the second (long condition). This involved deception as the second bout was only 20 min long. Cardiorespiratory variables, lactate, cadence, RPE, % associative thoughts, and affect (Feeling Scale, FS) were measured. Analysis was by Pearson correlations and a repeated-measures ANOVA at 2, 5, 8, 11, 14, 17, 20 min. Results: The psychological and physiological variables showed no differences between conditions. Physiological response was consistent with non-steady state exercise. RPE increased linearly (p<0.05) and ranged from about 12 to 14 in both bouts. Significant correlations between RPE and FS occurred at all time points in the short condition (r= -0.61 to -0.79), but in the long condition, correlations were only significant at 2, 5, and 8 min (r= -0.50 to -0.68). There were no significant correlations between RPE and any physiological variable or associative thoughts. Discussion: Expected duration did not alter RPE, which is inconsistent with Rejeski & Ribisl (1980) and Baden et al. (2004). This may be due to a different subject sample using different mental strategies. The significant RPE-FS correlations during the short condition were higher than reported by Rejeski & Ribisl (1980), who found a moderate but significant correlation of -0.45 at a similar intensity and RPE. In the long condition, the RPE-FS relationship ceased to be significant from 11 min onward. Hardy & Rejeski (1989) proposed that ambiguity in physiological cues during moderate exercise lessens the relationship, although it is not clear why this would emerge in one condition only. This may indicate a coping mechanism in response to a greater exercise challenge. As well, the data are consistent with the notion that RPE represents the progression toward absolute fatigue, which may happen independently of the progression of physiological variables (Noakes, 2008). In conclusion, RPE is not always affected by a change in anticipated exercise duration and seems to function as a stable measure of the progression toward exhaustion.